2002
DOI: 10.1007/s00415-002-0792-3
|View full text |Cite
|
Sign up to set email alerts
|

Timecourse of health-related quality of life as determined 3, 6 and 12 months after stroke

Abstract: Despite stable neurologic function and disability, global as well as domain-specific measures of QOL deteriorated over the 12-months observation period in a cohort of stroke survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
113
5
11

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(149 citation statements)
references
References 33 publications
16
113
5
11
Order By: Relevance
“…Earlier studies have also indicated that the most significant predictors of HRQOL are functional status and depression (3,4,10,(16)(17)(18)(19)25,36), although a study demonstrated a more generalized adverse effect on HRQOL than functional disabilities (37), and some who have demonstrated disability alone explained little regarding the variance in the QOL (2,38). The results produced from the current study demonstrated that the anxiety and depression scores in patients were significantly higher compared with those in controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies have also indicated that the most significant predictors of HRQOL are functional status and depression (3,4,10,(16)(17)(18)(19)25,36), although a study demonstrated a more generalized adverse effect on HRQOL than functional disabilities (37), and some who have demonstrated disability alone explained little regarding the variance in the QOL (2,38). The results produced from the current study demonstrated that the anxiety and depression scores in patients were significantly higher compared with those in controls.…”
Section: Discussionmentioning
confidence: 99%
“…Emotional alterations are often observed after stroke (14,15) that are generally associated with reduced QOL in stroke survivors (10,(16)(17)(18). Earlier studies have also indicated that the functional status and depression are significant predictors of HRQOL (3,19).…”
Section: Introductionmentioning
confidence: 99%
“…The often-used neurological and functional scales have limitations with regard to picking up changes in patient health, especially among minimally compromised individuals 2,3 . HRQoL not only focuses on deficits or compromised functioning, but also takes into consideration the fact that quality of life (QoL) is an inherent attribute of self-perception and is able to measure various aspects of patients' general health 4 .…”
mentioning
confidence: 99%
“…It should be noted that the outer modifiable factors (such as appropriate social support) also determine the long-term prognosis and must be taken into account. Other authors point out to the important impact of such disorders as depression on forecasting [19].…”
Section: Discussionmentioning
confidence: 99%